2001
DOI: 10.1007/s004150170241
|View full text |Cite
|
Sign up to set email alerts
|

Acanthocytosis and neurological disorders

Abstract: Acanthocytosis occurs because of ultrastructural abnormalities of the erythrocyte membranous skeleton resulting in reduced membrane fluidity. At least three hereditary neurological conditions are associated with it, although as yet the pathogenesis of the neurological features is unknown. In abetalipoproteinaemia, an autosomal recessive condition, vitamin E deficiency results in a progressive spinocerebellar syndrome associated with peripheral neuropathy and retinitis pigmentosa. Neuroacanthocytosis is also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 59 publications
1
41
0
4
Order By: Relevance
“…The pathogenesis of acanthocyte formation is still unclear. 28 Magnetic resonance imaging (MRI) has shown degeneration of the caudate and more generalised cerebral atrophy. Increased signal on T2-weighted MRI in the caudate and putamen is a common feature.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…The pathogenesis of acanthocyte formation is still unclear. 28 Magnetic resonance imaging (MRI) has shown degeneration of the caudate and more generalised cerebral atrophy. Increased signal on T2-weighted MRI in the caudate and putamen is a common feature.…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%
“…Its etiology is unknown. Acanthocytes develop secondary to ultrastructural abnormalities in the erythrocyte membrane (1,2). The percentage of acanthocytes in the peripheral blood varies between 5% and 50% in neuroacanthocytosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroacanthocytosis is a multisystemic, slowly progressive, neurodegenerative disease associated by chorea, dystonia, orofacial dyskinesia, tics, epilepsy, cognitive involvement, and behavioural changes (1,2). In its differential diagnosis, there can be many diseases such as Huntington disease (HD), Parkinson's disease, Tourette's syndrome, and Wilson's disease.…”
Section: Introductionmentioning
confidence: 99%
“…These disorders belong together because they are phenotypically similar, although genetically distinct (Danek et al 2001;Stevenson & Hardie 2001;Rampoldi et al 2002) suggested by failure to thrive and steatorrhea. Triglyceride and cholesterol levels, and levels of fat-soluble vitamins, are very low.…”
Section: Choreoacanthocytosis and The Mcleod Syndromementioning
confidence: 99%